Learning, skill acquisition, reading, and dyslexia - Eden, Guinevere; Flowers, D. Lynn. (Malden, MA : Wiley-Blackwell, 2008)
This volume, based on the 25th Rodin Remediation Conference, presents and assesses recent scientific discoveries regarding the etiology and treatment of dyslexia. The Rodin Remediation Academy, founded in 1984, has held 24 conferences and symposia dedicated to research on dyslexia.
Includes bibliographical references and index.
Keywords: Dyslexia -- Congresses; Reading ability -- Congresses; Learning ability -- Congresses